Nanoparticulate strategies for the five R's of traumatic spinal cord injury intervention: restriction, repair, regeneration, restoration and reorganization. (February 2014) - Kumar, Pradeep; Choonara, Yahya E; Modi, Girish; Naidoo, Dinesh; Pillay, Viness
Nanomedicinal approaches for spinal cord injury (SCI) intervention encompasses the use of nanoscale materials and devices that prevent primary to secondary injury transition and improvement in the anatomical, physiological and functional outcomes of SCI. This review provides an incursion into the advances in nanoparticle-based neurotherapeutics for SCI and focuses on neuroactive-loaded nanoparticles for localized delivery of therapeutic factors to the severed spinal cord, targeted or nontargeted systemic drug delivery and nanoenclatherated neuroscaffolds. Special emphasis has been placed on the use of metal nanoparticles and functionalized structures as 'drug-free' interventions in SCI. Despite the immense advancements in nanoscience, nanointerventions still pose key challenges that need to be resolved in SCI. Several combinatorial strategies are proposed for the reconstruction of spinal architecture via restriction of the secondary injury cascade, reparation of the tethered neural architecture, regeneration of axons, restoration of biochemical functions and reorganization of the topographical and cortical networks of the spinal cord.